The death of Jesus - Coetzee, J. M. 1940- (Text Publishing, 2019)
In The Childhood of Jesus, Simon found a boy, David, and they began life in a new land, together with a woman named Ines. In The Schooldays of Jesus, the small family searched for a home in which David could thrive. In The Death of Jesus, David, now a tall ten-year-old, is spotted by Julio Fabricante, the director of a local orphanage, playing football with his friends. He shows unusual talent. When David announces that he wants to go and live with Julio and the children in his care, Simon and Ines are stunned. David is leaving them, and they can only love him and bear witness. With almost unbearable poignancy J. M. Coetzee explores the meaning of a world empty of memory but brimming with questions
Keywords: Fiktionale Darstellung